Konsep Bimbingan Pribadi-Sosial dalam Mengembangkan Sikap Positif Siswa - K., Sulfikar (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2019)
This study discusses social personal guidance as an effort to develop positive mental attitudes in students. In social personal guidance is often related to environmental factors and traits, as well as various aspects need to be a concern of counselor understanding in dealing with service goals as a basis for diagnosis, and providing assistance to students. One of the social personal guidance services to carry out a counseling guidance for the development of positive mental attitude of students. The type of research used is library research (library research). which has the nature of qualitative descriptive research who wish to obtain analytical data on social personal guidance in an effort to form a positive mental attitude. The results of this study are the implementation of personal-social guidance services consisting of 4 stages, namely the planning stage, implementation stage, evaluation stage and follow-up. Forms of implementation of social personal guidance services with indirect methods include classical guidance, collaboration with homeroom teachers, classical guidance, collaboration with homeroom teachers, collaboration with parents, collaboration with related parties outside of school, home visits. The material presented includes motivation, self-confidence, self-esteem, self-adjustment, and emotional control. Forms of implementation with direct methods include individual guidance, group guidance, and individual counseling. Social personal guidance to develop and maintain positive mental attitudes of students.